Process improvement of conventional palm oil milling: continuous cooker - Azmi, Azlin Suhaida; Somasundaram, Mageswari; Jimat, Dzun Noraini (IIUM Press, 2011)
The objective of this study is to improve the conventional milling process in palm oil processing by replacing the function of the current used horizontal sterilizer with a Continuous Cooker. A trial study of Continuous Cooker was conducted and results showed that the cooker operated for 55 minutes using low pressure steam of 1 bar and cooking temperature of 98°C. At these operating conditions, the cooker was capable of carrying out the functions of a horizontal batch sterilizer by achieving most of the conventional sterilization purposes. This was proven by the results obtained from trial runs and laboratory analysis conducted on the equipment and its samples.